2017
DOI: 10.3758/s13414-017-1445-z
|View full text |Cite
|
Sign up to set email alerts
|

Are crossmodal correspondences relative or absolute? Sequential effects on speeded classification

Abstract: Crossmodal correspondences have often been demonstrated using congruency effects between pairs of stimuli in different sensory modalities that vary along separate dimensions. To date, however, it is still unclear the extent to which these correspondences are relative versus absolute in nature: that is, whether they result from pre-defined values that rigidly link the two dimensions or rather result from flexible values related to the previous occurrence of the crossmodal stimuli. Here, we investigated this iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
1
29
0
2
Order By: Relevance
“…That said, the last few years has seen the publication of a few intriguing papers showing that individuals with synaesthesia may be more susceptible to the influences of certain crossmodal correspondences than are non-synaesthetes (e.g., see [39], see also [40]). At the same time, however, it is also worth remembering that crossmodal correspondences are often characterized as being relative [41,42] -that is, it is the larger of two circles that is matched to the lower-pitched of two sounds, rather than there being any specific match between a sound having a particular pitch and an object of a specific size. By contrast, the relation between inducer and concurrent in the case of synaesthesia proper tends to be absolute.…”
Section: Correspondences Involving Simple Auditorymentioning
confidence: 99%
“…That said, the last few years has seen the publication of a few intriguing papers showing that individuals with synaesthesia may be more susceptible to the influences of certain crossmodal correspondences than are non-synaesthetes (e.g., see [39], see also [40]). At the same time, however, it is also worth remembering that crossmodal correspondences are often characterized as being relative [41,42] -that is, it is the larger of two circles that is matched to the lower-pitched of two sounds, rather than there being any specific match between a sound having a particular pitch and an object of a specific size. By contrast, the relation between inducer and concurrent in the case of synaesthesia proper tends to be absolute.…”
Section: Correspondences Involving Simple Auditorymentioning
confidence: 99%
“…Within each of the two brightness categories mapping onto different responses, heavinessbrightness congruence effect was insensitive to any gradations in the degree to which a stimulus is either brighter than the background, or darker than the background. Thus, the two brighter stimuli proved to be indistinguishable from each other in their contribution to the congruence effect, as did the two darker stimuli (see Brunetti, Indraccolo, Del Gatto, & Spence, 2018;Spence, 2019;and Walker, 2016a, for evidence for, and discussion of, the functional significance of the relative, rather than the absolute, coding of stimulus features as they contribute to correspondences).…”
Section: Discussionmentioning
confidence: 94%
“…While the exact mechanism behind this frequency effect remains unknown, the influence of the individual's exposure to or experience with the linguistic items and colours on their pairings seems obvious and hard to ignore. Third, in their investigation on pitch-size correspondence, Brunetti et al (2018) demonstrated that a mediumpitch tone when preceded by a high tone (thus, relatively low) was more likely to be paired with a large disk, whereas the same medium-pitch tone when preceded by a low tone (thus, relatively high) was more likely to be paired with a small disk. Hence, it was the individual's subjective conceptualisation of "high" vs "low" that mattered, not the absolute pitch of the tone.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in fundamental frequency (F0) of the stimuli is also quite large, e.g., 100-10 000 Hz in Marks (1974), either 174.6 Hz or 1046.5 Hz in Melara (1989), and 200-3417 Hz in Hubbard (1996), although de Thornley Head (2006) demonstrated that the pitch-lightness association could also be found in musical notes with a much narrower pitch range . This suggests that the pitch-lightness association is mapped relatively rather than absolutely (Brunetti et al, 2018).…”
Section: Association Between Pitch and Lightnessmentioning
confidence: 99%